2018
DOI: 10.1111/iej.13033
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage populations show an M1‐to‐M2 transition in an experimental model of coronal pulp tissue engineering with mesenchymal stem cells

Abstract: Aim To assess M1/M2 macrophage phenotypes in a coronal pulp regeneration model in rats, under the hypothesis that there are dynamic M1/M2 phenotype changes during the different stages of the pulp regeneration. Methodology The maxillary first molars of Wistar rats were pulpotomized, and biodegradable hydrogel‐made scaffolds carrying rat bone marrow mesenchymal stem cells were implanted in the pulp chamber. After 3, 7 and 14 days, samples were processed for (i) histological analysis and double immunoperoxidase s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 52 publications
(85 reference statements)
1
15
0
Order By: Relevance
“…In response to injury and subsequent healing, macrophages are capable of polarization towards a spectrum of phenotypes. Based on the environmental cues and molecular mediators, these cells will differentiate into either pro-inflammatory type I macrophage (M1) or anti-inflammatory type II macrophage (M2) phenotypes[ 25 - 27 ].…”
Section: Pbmc In Regenerationmentioning
confidence: 99%
“…In response to injury and subsequent healing, macrophages are capable of polarization towards a spectrum of phenotypes. Based on the environmental cues and molecular mediators, these cells will differentiate into either pro-inflammatory type I macrophage (M1) or anti-inflammatory type II macrophage (M2) phenotypes[ 25 - 27 ].…”
Section: Pbmc In Regenerationmentioning
confidence: 99%
“…It has become increasingly clear that different polarization states of Mφs exert different influences, most likely via paracrine action, on their cocultured cells in vitro (for example, see ) and their surrounding neighbors in vivo (for examples, see ). Although both the M1 and M2 phenotypes are involved in and necessary for many if not all wound healing cascades, a high ratio of wound healing Mφs normally leads to a favorable tissue regenerative outcome, which includes regeneration of the periodontium (for examples, see ). Therefore, modulating proper Mφ polarization to provide a delicate balance of cytokines and mediators is a critical target for tissue regeneration (for examples, see ).…”
Section: Introductionmentioning
confidence: 99%
“…Paula-Silva et al [4] found that TNF-α released from M1 macrophages promotes the odontogenic differentiation of dental pulp cells. However, macrophages undergo M1-to-M2 phenotypical switch in pulp tissue engineering, indicating that such macrophage transition is essential for building a suitable microenvironment for pulp tissue repair [9,10]. M2 macrophages can release odontogenic factors, such as BMP2, TGFβ1, and TGFβ3, to actively participate in odontogenesis [11][12][13].…”
Section: Dpscs-sev-stimulated Macrophages Enhance Odontogenic Differementioning
confidence: 99%
“…M1 macrophages exert proinflammatory functions through helper T (Th) type 1 (Th1)-associated immune reactions [7], whereas M2 macrophages enhance Th2-related reactions, downregulating inflammation [8]. Besides regulating immune reactions, macrophages affect the odontogenic differentiation of stem cells as well as dental pulp repair [9,10]. Macrophages can release regulatory factors such as BMP2, TGFβ1, and TGFβ3 [11][12][13], to actively participate in odontogenic differentiation of DPSCs [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation